Lifestyle of the nursing professionals of the Hospital Nacional Guillermo Almenara Irigoyen, Lima - Rafael Cabanillas, Rosa Cristina (2019)
Objective: to identify the lifestyle of the nursing professionals of the medical, surgical and traumatologyservices. Methods: a descriptive, non-experimental, cross-sectional study with a quantitative approach. For thedata collection, the questionnaire of Marcos (2012) was adapted by the researcher who measures the nursingprofessional's lifestyle. This questionnaire consists of 29 items that explore six dimensions of lifestyle: physicalactivity and sport, food, recreation, rest, stress management and consumption habits. The type of sampling wasnon-probabilistic, being intentionally selected 170 nurses. Results: Of the 100% (170) of nursing professionals,63.5% presented an unhealthy lifestyle and only 36.5% a healthy lifestyle. In the results by dimensions: physicalactivity and sport, healthy 35.9% and unhealthy 64.1%; Food, healthy 37.6% and unhealthy 62.4%; Recreation,healthy 37.1% and unhealthy 62.9%; Rest, healthy 31.2% and not healthy 68.8%; Stress management, healthy37.1% and unhealthy 62.9% and consumption habits, healthy 37.1% and unhealthy 62.9%. Conclusions: Theseresults suggest the need to invest in changes, from initiatives such as reflections on the "role of nursing self-care".It is important to highlight the implementation of educational strategies of the "Health Promotion and DiseasePrevention Programs" aimed at nursing professionals in order to reduce the probability of presenting unhealthybehaviors and decrease the imminent risks of morbidity, with The goal of making them responsible for theirdecisions to change their risk behaviors, more if they are considered to be role models for both their patients andthe community at large.